Safety of Pharmacotherapy in COVID-19 Patients: A Literature Review - A. V. Kryukov; A. S. Zhiryakova; Yu. V. Shevchuk; A. V. Matveev; V. I. Vechorko; O. V. Averkov; S. V. Glagolev; I. I. Temirbulatov; K. B. Mirzaev; N. P. Denisenko; Sh. P. Abdullaev; D. A. Sychev (Безопасность и риск фармакотерапии, 2022)
The safety of COVID-19 pharmacotherapy is a relevant issue, first of all, because of the current lack of experience with using particular medicinal products and with off-label prescribing. The aim of the study was to analyse information on potential adverse drug reactions (ADRs) and their predictors in etiology- and pathogenesis-oriented COVID-19 therapy. According to literature data, the main clinically significant risk factors for COVID-19 patients to develop an ADR are the duration of their hospital stay, combined use of antivirals, polypharmacy, and their history of drug allergies. The most common adverse reactions to antivirals, to virus-neutralising antibodies, and to human anti-COVID-19 immunoglobulin and convalescent plasma are, respectively, gastrointestinal and hepatobiliary disor ders; gastrointestinal disorders, neurological disorders, and allergic reactions; and transfusion reactions (fever, chills, etc.). For pathogenesis-oriented therapy with systemic glucocorticosteroids, the most characteristic ADR is hyperglycaemia. Janus kinase inhibitors and interleukin inhibitors are most often associated with gastrointestinal disorders and hypertransaminasemia; neutropenia is also characteristic of a number of interleukin inhibitors. Haemo static adverse reactions to anticoagulants depend on the patient’s dosing regimen and condition. Drug-drug interactions are a common problem in COVID-19 treatment, with the combination of nirmatrelvir and ritonavir showing the largest number of significant interactions attributed to their pharmacokinetics. Currently, there is data on the role of pharmacogenetic biomarkers in the safety and clinical outcomes of COVID-19 therapy. Thus, to improve the safety of COVID-19 therapy, an integrated approach is needed that will take into account both the clinical, demographic, and pharmacogenetic predictors of ADRs and the risk of drug-drug interactions.